2009
DOI: 10.1039/b818369d
|View full text |Cite
|
Sign up to set email alerts
|

Discrete, multi-component complexes with cucurbit[8]uril in the gas-phase

Abstract: The formation of modular, multi-component, host-guest complexes stable both in water and in the gas-phase is described; by modulating the stoichiometry of the different subunits in aqueous solution, quantitative self-assembly of the predicted and desired architecture is achieved, even allowing for ABA triblock copolymer assemblies stable in the gas-phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 16 publications
1
79
0
Order By: Relevance
“…24,[28][29][30][31][32] This host has been used most prominently in a 1:1:1 'hetero'-ternary complex using an electron-deficient first guest, such as methyl viologen (MV), and an electron-rich second guest such as naphthol, pyrene and dibenzylfuran. 30,[32][33][34] In favorable cases, exceptionally high overall equilibrium binding affinities (K eq (overall) = K eq (1) × K eq (2) up to 10 14 M −2 ) were reported, 26,30,33,35 leading to utilization in a number of applications ranging from the formation of diblock copolymers, [36][37][38] sequence-selective recognition of peptides, 39 3 self-sorting systems, 40 surface modification, 41,42 protein conjugation, 43 to the formation of nanocapsules, 44 nanocomposites 45 and hydrogels. [46][47][48][49] Urbach and coworkers first demonstrated that N-terminally charged aromatic amino acids, such as phenylalanine and tryptophan, bind in a 2:1 fashion forming a 'homo'-ternary complex with CB [8] through multiple non-covalent interactions acting synergistically.…”
Section: Introductionmentioning
confidence: 98%
“…24,[28][29][30][31][32] This host has been used most prominently in a 1:1:1 'hetero'-ternary complex using an electron-deficient first guest, such as methyl viologen (MV), and an electron-rich second guest such as naphthol, pyrene and dibenzylfuran. 30,[32][33][34] In favorable cases, exceptionally high overall equilibrium binding affinities (K eq (overall) = K eq (1) × K eq (2) up to 10 14 M −2 ) were reported, 26,30,33,35 leading to utilization in a number of applications ranging from the formation of diblock copolymers, [36][37][38] sequence-selective recognition of peptides, 39 3 self-sorting systems, 40 surface modification, 41,42 protein conjugation, 43 to the formation of nanocapsules, 44 nanocomposites 45 and hydrogels. [46][47][48][49] Urbach and coworkers first demonstrated that N-terminally charged aromatic amino acids, such as phenylalanine and tryptophan, bind in a 2:1 fashion forming a 'homo'-ternary complex with CB [8] through multiple non-covalent interactions acting synergistically.…”
Section: Introductionmentioning
confidence: 98%
“…In the present study, for the first time, we report on the noncovalent interaction of CB [6] with anionic molecules on its exterior, and their chemical reactions in the gas phase using electrospray ionization mass spectrometry (ESI-MS). ESI-MS is a proven technology to study the intrinsic chemistry of supramolecular complexes in the absence of solvent effects [19], including host-guest chemistry of CB[n] supramolecular complexes [20][21][22][23][24][25]. Especially, interfacing ion mobility spectrometry with ESI-MS has become a powerful tool for screening the structures of supramolecular complexes [26][27][28][29][30].…”
mentioning
confidence: 99%
“…An inclusion complex of the electron acceptor 2,7-dimethyldiazapyrenium (34) with an equivalent of Q [8] provided effective recognition and detection of electron-donating guests (Scheme 12), particularly catechol (35) solution or on the surface of silica particles [58]. The Q[8]-induced assembly of polymers with viologen and naphthol terminal groups should be useful for predictable polymerization with applicable functionalization in electrochemistry and optics-mediated supramolecular strategy [59,60]. The same work principle has been introduced to operate redox-driven supramolecular devices and machines [61][62][63].…”
Section: Cucurbit[8]uril-induced Chemical Controlmentioning
confidence: 98%